Effect of Couples Counseling Based on the Problem-Solving Approach on the Fear of Delivery, Self-Efficacy, and Choice of Delivery Mode in the Primigravid Women - Ahmadi L; Karami S; Faghihzadeh S; Jafari E; Dabiri Oskoei A; Kharaghani R (Zanjan University of Medical Sciences and Health Services, 2018)
Background: Fear is an important factor that causes pregnant women to opt for cesarean section. Women with the fear of childbirth consider labor pain to be beyond their power. Basically, these women request cesarean section only to avoid normal vaginal delivery, which indicates their low self-efficacy in normal vaginal delivery. Objectives: The present study aimed to investigate the effects of couples counseling based on the problem-solving approach on the fear of delivery, self-efficacy, and choice of delivery mode in the primigravid women requesting elective cesarean section in Zanjan, Iran. Methods: This quasi-experimental study was conducted on 76 pregnant women in the second trimester of pregnancy and their spouses. The women were eligible for elective cesarean section and met the inclusion criteria. The intervention was based on the problem-solving counseling approach with the couples, which was performed in three weekly sessions at the clinic of Shahid Beheshti Hospital in Zanjan, Iran. Data were collected using the questionnaires of knowledge and attitude, Wijma delivery expectancy/experience questionnaire, and Louis' self-efficacy scale at the baseline and after one month of the final session. Data analysis was performed using independent t-test, Chi-square, and one-way analysis of variance (ANOVA). Results: Significant differences were observed in the mean scores of knowledge and attitude of women and men, and fear of delivery and self-efficacy of women between the intervention and control groups after counseling (P<0.001). The women in the intervention group were significantly more likely to do normal delivery compared to the control group (P<0.001). Conclusion: According to the results, couples counseling based on the problem-solving approach could be effective in reducing the fear of delivery and increasing the self-efficacy of primigravid women. Furthermore, it could improve the knowledge and attitude of couples, thereby decreasing the rate of cesarean section and tendency toward this mode of delivery.